Perception of Diploma in Accountancy students on ethics education - Zainal Abidin, Nor Sharizad; Abdul Hamid, Fatima (2017)
The aim of this study is to determine the perception of Diploma in Accountancy (DIA) students on whether ethics should be integrated into the DIA curriculum.This study also investigates the reasons for their opinion.In order to meet these objectives, 100 questionnaires were distributed to final year DIA students of Kolej Professional MARA (KPM).Based on the findings from 96 respondents, two-thirds majority were in support of ethics education in the DIA programme.These students, who agree to ethics integration, were primarily of the opinion that ethics was crucial to the accounting profession, and if ethics were not taught, ethical scandals involving the profession would persist.On the other hand, the one-third minority, who disagree that ethics should be integrated, were mainly of the opinion that there were insufficient materials to teach ethics, accounting lecturers were unwilling or lacked qualifications to teach ethics, and ethical training could not take place in a classroom setting.These concerns of the DIA students should be taken into consideration by the Ministry of Education (MOE) and KPM, should they want to be in line with Halatuju 3.